Type III Secretion System of Aeromonas salmonicida Undermining the Host's Immune Response - Frey, Joachim; Origgi, Francesco C. (Frontiers in Marine Science, 2016)
Aeromonas salmonicida subsp. salmonicida is an important pathogen in salmonid aquaculture and is responsible for furunculosis, a common infectious disease in salmon, trout and char. The type-three secretion system (T3SS) is considered as the major virulence attribute of A. salmonicida. It is used by the bacterium to secrete and translocate a large number of toxins and effector proteins into the host cell. Some of these factors such as the bi-functional ADP ribosylating—GTPase activating protein AexT have been shown to have a detrimental impact on the integrity of the cell cytoskeleton, and hence contribute to impair phagocytosis. Other effector proteins that are injected to the host cell such as AopP act by inhibiting the NF-κB signaling pathway blocking the translocation of NF-κB (p65) into the nucleus, thus influencing the host's inflammatory response. Several additional effectors that are secreted and translocated via the T3SS including Ati2, AopN, and ExsE have been suggested to modulate the host's immune response in particular by down regulating the inflammatory reaction. The analysis of the immune response in rainbow trout (Oncorhynchus mykiss) infected with virulent, T3SS harboring A. salmonicida subsp. salmonicida revealed that the infection leads to a rapid and strong downregulation of several immune-relevant markers affecting both the innate and the adaptive immune response, leading to mortality of the infected fish. These findings show that T3SS-delivered effector molecules and toxins of A. salmonicida impair the host's cytoskeleton thus damaging cell physiology and phagocytosis, but also affect the host's immune defense.